2020
DOI: 10.1002/mas.21643
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry‐based Techniques for Direct Quantification of High Ionization Energy Elements in Solid Materials—challenges and Perspectives

Abstract: The determination of nonmetals, first of all, the most electronegative ones—nitrogen, oxygen, fluorine, chlorine, and bromine, poses the highest challenge for element analysis. These elements are characterized by high reactivity, volatility, high ionization energy, and the absence of intensive spectral lines in the optical spectral range. Conventional techniques of their quantification include considerable “wet chemistry” stages so the application of these techniques for the solid sample is highly laborious an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 218 publications
(324 reference statements)
0
7
1
Order By: Relevance
“…to the amount of the constituent element in the sample) have probably higher ionization efficiency as compared to the other elements in argon plasma. The general impression about chlorine is that due to the higher ionization energy and higher electronegativity, it has lower ionization rates in argon plasma, 30 however, contrary to expectations a different behaviour is noticed here. It should be noted that the most probable ionization process is only electron impact ionization of the chlorine ground state.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…to the amount of the constituent element in the sample) have probably higher ionization efficiency as compared to the other elements in argon plasma. The general impression about chlorine is that due to the higher ionization energy and higher electronegativity, it has lower ionization rates in argon plasma, 30 however, contrary to expectations a different behaviour is noticed here. It should be noted that the most probable ionization process is only electron impact ionization of the chlorine ground state.…”
Section: Resultscontrasting
confidence: 93%
“…Therefore, in general, chlorine has lower sensitivity as compared to most metallic constituent elements present in the matrix. 30,31 The most intense atomic emission lines of chlorine either require vacuum-UV (for 132.72 nm) or NIR (for 837.59 nm) sensitive detection systems. Additionally, the complication in chlorine quantication further arises when it is present in the matrix as a constituent element in ultratrace amounts.…”
Section: Analytical Challenges Of Mocl 2 O 2 Analysis In Solid (Akes...mentioning
confidence: 99%
“…Under such repelling pulse delay, the ions formed by the high-energy electron packet are detected. 11,17,18 The flow of the high-energy electron packet is formed at the front of the discharge pulse and is capable to ionise the components with the highest ionisation energies. 9,11 The obtained mass spectrum (Fig.…”
Section: No + + M → No + M +mentioning
confidence: 99%
“…Recently, glow discharge (GD) sources, formerly considered mainly as a source suitable for inorganic and isotopic analysis [ 17 ], have gained an increased level of attention in relation to the analysis of VOCs and volatile inorganic molecules mixtures [ 18 ]. Nunome et al [ 4 , 19 ] reported the determination of VOCs in the air using a Soft Penning ionization (SPI) GD source.…”
Section: Introductionmentioning
confidence: 99%